Pengaruh Rasio Maltodekstrin dan Gum Arab Terhadap Aktivitas Antioksidan dan Warna Serbuk Terung Belanda (Solanum betaceum Cav) Yang Terkopigmentasi - Roulina Hutasoit, Lewi Rensia; Diah Puspawati, Gusti Ayu Kadek; Mayun Permana, I Dewa Gde (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i02.p05, 2023)
The study aimed to know the effect of the ratio maltodextrin and gum arabic on the antioxidant activity and color of the copigmentation tamarillo powder and to proper ratio of maltodextrin and gum arabic to get the copigmentation tamarillo powder with the best antioxidant activity and color by foam mat drying method. The study used a completely randomized design (CRD) with ratio of maltodextrin and gum arabic treatment consisting of five levels, there were 5:0, 4:1, 3:2, 2:3, 1:4. All treatments were repeated three times in order to obtain 15 experimental units. The data were analyzed statistically using the variance test and if the treatment had a significant effect to observed variables, it was continued with Duncan's Multiple Range Test (DMRT). The result showed that the ratio of maltodextrin and gum arabic had a significant effect (P<0,05) on water content, ash content, solubility, total anthocyanin, total phenol, antioxidant activity, and color intensity. The ratio of maltodexstrin and arabic gum (1:4) was the best treatment to produce copigmentation tamarillo powder with the total anthocyanin 41.97 mg/100g, total phenol 125.57 mg GAE/100g, antioxidant activity 78.05%, value L* 47.10, a* 44.03, b* 23.97, chroma 50.14, °Hue 28.56 (red color), water content 3.92% and solubility 83.90%